Unit Commitment with Battery Energy Storage Considering Wind Forecast Error - Cai Zhi; Zeng Lili; Zhao Kun; Men Deyue; Zhao Xu; Xu Dan; Dai Sai (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The integration of wind resource into the electric grid brings significant challenges due to the variable nature and anti-peak-regulation characteristic of wind power. Based on least square method, an improved normal distribution model is proposed to fit the actual wind power forcast error. Furthermore, considering wind power forecast error and the great potential of battery energy storage system (BESS) technology to mitigate the impact of volatile wind power, a unit commitment (UC) model with large capacity BESS has been estanbished in this study. Case studies with modified IEEE 39-bus system are employed to validate the proposed method. The role of BESS on economics, peak load shifting and accommodating wind power is discussed. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.4937